PEMBERDAYAKAN MASYARAKAT DESA AUNUPE DALAM PENGELOLAAN HAMA DAN PENYAKIT TANAMAN YANG RAMAH LINGKUNGAN - Andi Khaeruni; Rahayu Rahayu; Gusti Ayu Kade Sutariati; Tresjia C. Rakian (Jurnal Hilirisasi IPTEKS, 2020)
Aunupe Village, Wolasi District is one of the villages for the development of organic vegetables in Konawe Selatan Regency. The frequent occurrence of high levels of pest and disease attacks is the main reason for the use of synthetic pesticides that are not justified in organic farming systems. On the other hand, in the same location, there is a group of women farmers who are not productive. Both of these problems can be overcome if the farmer women's group produces quality biological agents that can be utilized by horticultural farmers in an environmentally friendly cultivation system. The implementation of the PKM Program in Aunupe Village is very appropriate as a means and media for transferring technology on how to increase the productivity of environmentally friendly vegetable plants by developing organic farming techniques. Control of pests and plant diseases by using biological agents and botanical pesticides is a wise choice in efforts to increase agricultural production with high economic value while maintaining biodiversity to support sustainable agricultural cultivation, especially in the cultivation of vegetable crops as a source of community nutrition.